Thrombosis as the First Manifestation of Granulomatosis with Polyangiitis Disease in an Adolescent - Mohsen Jari (Case Reports in Hematology)
Background. Granulomatosis with polyangiitis disease (GPA) is a rare vasculitis characterized by granulomatous inflammation of respiratory tracts, glomerulonephritis, and vasculitis of other organs. Case Presentation. A 13-year-old girl was referred due to swelling and pain on her left arm. The Doppler and compression ultrasonography showed noncompressible left brachial and axillary vein thrombosis. Sinus computed tomography (CT) demonstrated pansinusitis, and spiral chest CT showed alveolar hemorrhage. Laboratory tests showed hematuria, proteinuria, and highly positive antineutrophil cytoplasmic antibody (cANCA). Laboratory tests of coagulopathy were normal. The patient was recognized as a case of GPA. Conclusion. Although GPA is not frequently associated with thrombosis especially in children, this is the first report that shows thrombosis may be the first manifestation of GPA in an adolescent.